2021
DOI: 10.1016/j.strueco.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

From FDI to economic complexity: a panel Granger causality analysis

Abstract: In this paper, we assess whether attracting higher amounts of FDI induces a greater level of economic complexity in a country. Using a panel of 117 countries and 22 years, from 1995 to 2016, we test for the causal relationship between inward FDI and economic complexity using a panel Granger causality approach. We also estimate the short-run relationship between these two factors using a panel vector autoregressive model and an impulse response function approach. We find that accumulating a higher stock of inwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Li et al (2021) have also obtained that the deregulation of FDI inflows that took place in 2002 in different China's industries, has led to a greater level of export product sophistication. However, Antonietti and Franco (2021) have found empirical evidence that FDI inflows (Granger) cause economic complexity 6 in developing countries.…”
Section: Theoretical Discussion On the Effect Of Economic Complexity On Services Export Diversificationmentioning
confidence: 99%
“…Li et al (2021) have also obtained that the deregulation of FDI inflows that took place in 2002 in different China's industries, has led to a greater level of export product sophistication. However, Antonietti and Franco (2021) have found empirical evidence that FDI inflows (Granger) cause economic complexity 6 in developing countries.…”
Section: Theoretical Discussion On the Effect Of Economic Complexity On Services Export Diversificationmentioning
confidence: 99%
“…[11] Antonietti and Franco (2021) have, however, obtained that economic complexity does not (Granger) cause FDI in ows.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…Li et al (2021) have uncovered that the liberalization of FDI in 2002 on different industries in China, has had a positive effect on export sophistication. Meanwhile, Antonietti and Franco (2021) have demonstrated empirically that FDI in ows (Granger) cause economic complexity, but that economic complexity does not (Granger) cause FDI in ows in developing countries.…”
Section: Do Fdi In Ows Matter For the Effect Of Nrtps On Economic Complexity?mentioning
confidence: 99%
“…Countries that improve their level of economic complexity can attract FDI in ows (e.g., Gómez-Zaldívar et al 2021) because MNEs may choose to set up plants in countries that manufacture complex products, given the speci c advantages of these countries in terms of productive knowledge and exclusive capabilities. Gómez-Zaldívar et al (2021) and Sadeghi et al (2020) have found evidence that countries with greater economic complexity attract higher FDI ows, while Antonietti and Franco (2021) have uncovered that economic complexity does not (Granger) cause FDI ows to developing countries. In spite of the unconclusive outcomes of the limited existing literature on the effect of economic complexity on FDI in ows, we do consider the variable "FDI" as endogenous in the present analysis.…”
Section: Econometric Approachmentioning
confidence: 99%